Using Different Methods to Tenderize Spent Hens Meat - Al-Hajo, N.A. Nadia (International Journal of Poultry Science, 2008)
The aim of this study is tenderizing spent hens meat by using cheap local materials such as bitter orange juice, vinegar, salt and sugar for 1,2, 3 and 4h, distill water is used (T1) in curing to make it as standard. Bitter orange juice (acidity of 1.5) (T2), vinegar (acidity of 7) (T3), table salt (2%) (T4) and sugar (2%) (T5) were used. The processed meat was storied under -18oC ± 2oC for a month to investigate the influence of the type of treatment and the periods of storing and submersion on the sensory properties and chemical qualities through estimating the percentage of moisture, hydrogen number pH, volume of the released extract. A sensory properties evaluation of the qualities of flavor, juiciness, tenderness and overall acceptance was carried out. Results of curing in the different solutions revealed a decreased pH value in (T2) and T3 ; while the highest significant differences (p